Knight's Microsoft SQL Server 2012 integration services 24-hour trainer - Knight, Brian; Knight, Devin; Davis, Mike; Snyder, Wayne (Wrox programmer to programmer, 2013)
If you need a practical, hands-on introduction, especially to SQL Server Integration Services (SSIS), this book-and-video package from authority Brian Knight is the perfect solution. Each lesson includes three major components: a description of how each SSIS feature or process works, a tutorial that walks you through the process or technique, and an accompanying video lesson. It's a complete learning package that will give you the confidence you need to start your first SSIS project. Guides novice database administrators and developers who are learning Microsoft SQL Server 2012 and SQL Server Integration Services (SSIS) Provides expert instruction from leading SQL Server authority and author, Brian Knight Includes a book and a video, complete instruction that includes lessons, hands-on tutorials, and video demonstrations by the author Covers the very latest changes and updates in the SQL Server 2012 release Microsoft SQL Server 2012 Integration Services 24-Hour Trainer makes SQL Server 2012 and SSIS much less intimidating. Note: CD-ROM/DVD and other supplementary materials are not included as part of the e-book file, but are available for download after purchase.